ANALISIS PEMAHAMAN MATEMATIS SISWA KELAS VIII B SMP NEGERI 8 JEMBER BERDASARKAN POLYA DENGAN PEMBERIAN SCAFFOLDING POKOK BAHASAN KUBUS DAN BALOK - Safitri, Fihrin Luqiyya; Susanto, Susanto; Fatahillah, Arif (Kadikma, 2017)
Abstract. The ability of mathematical understanding is one of the purposes in learning activity. By giving understanding that the materials that have been taught to the students is not only as memorizing, but it is more as the students’ understanding in mathematical conceptual, especially in lesson Cube and Cuboids. The ability of understanding is categorized as three levels, they are high, medium, and low understanding. The research shows that of 35 students grouped based on the level the ability understanding mathematical students in accordance with test results obtained with 22 students to the ability of understanding high, 11 students to the ability of understanding and 2 students to the ability of understanding low. The student with high understanding has 4 types, while student who with​ medium level has 2 types, and student with low understanding has only 1 type. Scaffolding that is given to the students is based on the scaffolding characteristics by Roehler and Cantlon, in the stage of mechanical understanding is in characteristics inviting student participation and offering explanations, in the stage of inductive understanding is in characteristics inviting student participation and verifying and clarifying understandings, in the stage of rational understanding is in characteristics inviting student participation and modeling of desired behaviors, while in the stage of intuitive understanding is in characteristics inviting student participation, offering explanations and inviting student to contribute clues. The result of analysis using scaffolding method is the students are more able to understand accurately, but this method is not effective to be used because it spends much time in learning process, so this method will be more effective if it is used outside the learning process or it can be developed by using peer teaching. Keywords : Mathematics, Understanding, Scaffolding